Distributed AC Optimal Power Flow using ALADIN *. Issue 1 (July 2017) - Engelmann, Alexander; Mühlpfordt, Tillmann; Jiang, Yuning; Houska, Boris; Faulwasser, Timm
Abstract: This paper investigates the distributed solution of non-convex ac power flow optimization problems arising in electrical grids. Specifically, we consider the application of a recently proposed Augmented Lagrangian Based Alternating Direct Inexact Newton (aladin) scheme to ac optimal power flow problems. Using standard reformulations, we show how aladin can be applied to electrical grids of generic topology. We draw upon an ieee 5-bus system to demonstrate that aladin offers the potential to outperform common admm schemes.